Deletion of a dynamic surface loop improves stability and changes kinetic behavior of phosphatidylinositol‐synthesizing Streptomyces phospholipase D. Issue 4 (30th November 2013) - Damnjanović, Jasmina; Nakano, Hideo; Iwasaki, Yugo
ABSTRACT Supplementary phosphatidylinositol (PI) was shown to improve lipid metabolism in animals, thus it is interesting for pharmaceutical and nutritional applications. Homogenous PI can be produced in transphosphatidylation of phosphatidylcholine (PC) with myo‐inositol catalyzed by phospholipase D (PLD). Only bacterial enzymes able to catalyze PI synthesis are Streptomyces antibioticus PLD (SaPLD) variants, among which DYR (W187D/Y191Y/Y385R) has the best kinetic profile. Increase in PI yield is possible by providing excess of solvated myo‐inositol, which is achievable at high temperatures due to its highly temperature‐dependent solubility. However, high‐temperature PI synthesis requires the thermostable PLD. Previous site‐directed combinatorial mutagenesis at the residues of DYR having high B‐factor yielded the most improved variant, D40H/T291Y DYR, obtained by the combination of two selected mutations. D40 and T291 are located within dynamic surface loops, D37‐G45 (termed D40 loop) and G273‐T313. Thus, in this work, thermostabilization of DYR SaPLD was attempted by rational design based on deletion of the D40 loop, generating two variants, Δ37‐45 DYR and Δ38‐46 DYR PLD. Δ38‐46 DYR showed highest thermostability as its activity half‐life at 70°C proved 11.7 and 8.0 times longer than that of the DYR and Δ37‐45 DYR, respectively. Studies on molecular dynamics predicted Δ38‐46 DYR to have the least average RMSD change as temperature dramatically increases. At 60 and 70°C, both mutants synthesized PI in a twofold higher yield compared to the DYR, while at the same time produced less of the hydrolytic side‐product, phosphatidic acid. Biotechnol. Bioeng. 2014;111: 674–682. © 2013 Wiley Periodicals, Inc.